1999
DOI: 10.1556/aalim.28.1999.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Viability of Bifidobacteria by Microentrapment and Their Effect on Some Pathogenic Bacteria in Stirred Yoghurt

Abstract: Fifteen batches of stirred yoghurt were made to study the effect of microentrapment on the viability of bifidobacteria and their ability to inhibit the growth of E. coli and Staph. aureus. Entrapped cells of Bifidobacterium bifidum and Bifidobacterium infantis were able to produce antimicrobial agents which inhibited E. coli and Staph. aureus used as test organisms. Viable counts of unentrapped bifidobacteria decreased sharply, while entrapped cells of bifidobacteria were quite stable during refrigerated stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Furthermore, microencapsulation with resistant starch may improve viable cells of bacteria in acidic foods. This finding is in agreement with those of Kebary and Hussein (1999), Sultana et al (2000), Krasaekoopt et al (2003), Homayouni et al (2008) and Mirzaei et al (2012). The himaize starch could give a higher survival ability of probiotics (10 5 to 10 6 /g) in acidic environment of mayonnaise sauce.…”
Section: Survival Of Free and Encapsulated Bacteria In Mayonnaise Saucesupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, microencapsulation with resistant starch may improve viable cells of bacteria in acidic foods. This finding is in agreement with those of Kebary and Hussein (1999), Sultana et al (2000), Krasaekoopt et al (2003), Homayouni et al (2008) and Mirzaei et al (2012). The himaize starch could give a higher survival ability of probiotics (10 5 to 10 6 /g) in acidic environment of mayonnaise sauce.…”
Section: Survival Of Free and Encapsulated Bacteria In Mayonnaise Saucesupporting
confidence: 90%
“…A limiting factor in survival of probiotic bacteria has been reported as low pH (3.6 to 4.6) of mayonnaise sauce owing to the concentration of acetic acid (Radford and Board, 1993;Khalil and Mansour, 1998). It has been proven that microencapsulated probiotics survive better in acid conditions (Khalil and Mansour, 1998;Kebary and Hussein, 1999;Mokarram et al, 2009;Nazzaro et al, 2009;Chávarri et al, 2010;Brinques and Ayub, 2011;Su et al, 2011). Alginate microcapsules can be prepared by emulsion and extrusion techniques.…”
Section: Introductionmentioning
confidence: 99%
“…). Similarly, other encapsulating materials such as alginate (Kebary and Hussein ), alginate–starch (Adhikari et al . ) and κ‐carrageenan have been observed to improve survival of probiotic Bifidobacterium species in fermented dairy foods under refrigerated storage.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was observed that capsules containing prebiotics could provide the carbon and nitrogen sources for encapsulated probiotics leading to higher survival rates for Bifidobacterium and Lactobacillus in milk (Chen et al 2005). Similarly, other encapsulating materials such as alginate (Kebary and Hussein 1999), alginate-starch (Adhikari et al 2000) and j-carrageenan have been observed to improve survival of probiotic Bifidobacterium species in fermented dairy foods Table 2 Survival of free and encapsulated Bifidobacterium animalis subsp. lactis BB-12 after incubation in simulated gastric juice (pH 2) at 37°C for 30, 60, 90 and 120 min and in simulated intestinal juice pH (7.5) at 37°C for 2 h (value represents both after gastric and intestinal digestion in vitro).…”
Section: Changes Of Survival Rate Of Encapsulated and Free Bacterial mentioning
confidence: 99%
“…Such drug delivery vehicles can also be used to prevent the release of unwanted materials into the environment and extend the shelf life of the encapsulated materials (Zuidam & Shimoni ; Huq et al . ) and ensures a target‐specific delivery of bioactives in a host (Kebary & Hussein ; Picot & Lacroix ). Delivery of bioactives in aquaculture farms is a new challenge to formulation scientists.…”
Section: Introductionmentioning
confidence: 99%